1991
DOI: 10.1002/ajh.2830370402
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of poly(ADP‐ribose) synthetase gene in malignant lymphoma

Abstract: Over-expression of cellular protooncogenes has been proposed to function in the initiation and maintenance of malignancies. In order to distinguish malignant lymphoma from reactive proliferative diseases, we surveyed the expression levels of three protooncogenes(c-myc, c-fos and c-myb) in malignant lymphoma and reactive proliferative diseases. An increased level of c-myc or c-fos mRNA was observed in one case, respectively, out of three malignant lymphomata. The other cases exhibited no enhancement in protoonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…Consistent with these findings are the data from a number of PARP inhibitors based on nicotinamide analogues, ranging from those with low micromolar activity, such as 3-aminobenzamide (Durkacz et al, 1980) to the more potent and specific PARP inhibitors that have been generated more recently (Southan and Szabo, 2003;Curtin, 2005;Farmer et al, 2005;Ratnam and Low, 2007). Enhanced PARP-1 expression or activity has been observed in a number of different tumour cell lines (Tomoda et al, 1991;Shiobara et al, 2001) and could provide a greater level of resistance to both endogenous genotoxic stress, as well as to DNA damage-inducing therapeutic agents. Evidence that PARP inhibitors can sensitize tumour cells to cytotoxic therapies such as temozolomide, topoisomerase I inhibitors, platinums and radiation (for example Calabrese et al, 2004;Miknyoczki et al, 2003;Chalmers et al, 2004) has consequently provided sufficient interest for a number of these compounds to be developed as clinical candidates (see Table 2 and Plummer, 2005;Fong et al, 2006).…”
Section: Inhibitors Of Parpsupporting
confidence: 72%
“…Consistent with these findings are the data from a number of PARP inhibitors based on nicotinamide analogues, ranging from those with low micromolar activity, such as 3-aminobenzamide (Durkacz et al, 1980) to the more potent and specific PARP inhibitors that have been generated more recently (Southan and Szabo, 2003;Curtin, 2005;Farmer et al, 2005;Ratnam and Low, 2007). Enhanced PARP-1 expression or activity has been observed in a number of different tumour cell lines (Tomoda et al, 1991;Shiobara et al, 2001) and could provide a greater level of resistance to both endogenous genotoxic stress, as well as to DNA damage-inducing therapeutic agents. Evidence that PARP inhibitors can sensitize tumour cells to cytotoxic therapies such as temozolomide, topoisomerase I inhibitors, platinums and radiation (for example Calabrese et al, 2004;Miknyoczki et al, 2003;Chalmers et al, 2004) has consequently provided sufficient interest for a number of these compounds to be developed as clinical candidates (see Table 2 and Plummer, 2005;Fong et al, 2006).…”
Section: Inhibitors Of Parpsupporting
confidence: 72%
“…A higher level of PARP-1 mRNA was observed in malignant lymphoma cells compared with normal lymph nodes (Tomoda et al, 1991) and in colorectal adenocarcinoma biopsies compared with adjacent non-tumour tissues and hyperplastic polyps (Nosho et al, 2006). Evaluation of PARP-1 protein expression in hepatocellular carcinoma (HCC) by western blotting revealed that it was significantly increased in HCC, especially moderately differentiated, compared with the non-tumour samples (Shimizu et al, 2004).…”
mentioning
confidence: 94%
“…For example, PARP mRNA levels were found to be enhanced in malignant lymphomas but not in normal lymph nodes or reactive proliferative lymph nodes (17). Elevated PARP activity was identified in peripheral lymphocytes from patients with low-grade malignant non -Hodgkin's lymphoma (18), hepatocellular carcinomas (19,20), small-cell lung cancer lines (21), cervical cancer cells from patients (22), and the prostate cancer cell line LnCaP (23).…”
Section: Introductionmentioning
confidence: 99%